Molecular Mechanism of Inhibition of Cell Proliferation: An In Silico Study of the Active Compounds in Curcuma longa as an Anticancer - Selliana Maretha Wijaya Kusuma; Didik Huswo Utomo; R Susanti (Universitas Gadjah Mada, 2022)
Cancer is one of the death causes in the world. Many plants act as anticancer, one of them is Curcuma longa. The purpose of this study was to analyze the molecular mechanism of compounds in Curcuma longa as an anticancer using in silico. These research methods included exploration of the active compounds of Curcuma longa plants, prediction of their activity, human intestinal absorption test, test of Lipinski's rule of five, molecular docking, and interactions of receptor with compounds as well as signaling pathways. The results showed that Curcuma longa had 20 compounds that have the potential as an anticancer. As many as 5 of the 20 active compounds, namely α-curcumene, curcumenol, curcumin, curcumin II, and curcumin III had a value of Pa > 0.3 and HIA above 80%. The results of molecular docking of α-curcumene, curcumenol, curcumin, curcumin II, and curcumin III compounds with protein receptors of VEGFR-2, EGFR, and FGFR-1 showed ∆Gbind values of -5.0 to -7.5 kcal/mol. The compound in Curcuma longa that had the most effective activity as an anticancer was curcumin with a ∆Gbind value of -7.5 kcal/mol at the FGFR-1 receptor. Curcumin molecular mechanism as antiproliferative was revealed computationally through inhibition of the PI3K/AKT/mTOR pathway.